Socio-Economic Formation of the Cluster in Tourism - Amriddinova R; L.X. Abidinova (International Journal on Economics, Finance and Sustainable Development, 2021)
This article discusses the creation of a cluster system in tourism, its organizational and institutional framework. In addition, practical insights into the experience of using cluster methods in the development of regional competitiveness and the market of tourism services are based on the interpretation of scientists. Opportunities for the establishment of tourist clusters have been identified